Model Pembelajaran Tenses Menggunakan Rumus Mathematic English (MatEng) - Muhammad Shofiyuddin; Santi Andriyani (LP2M IAIN Sultan Amai Gorontalo, 2019)
Tenses mastery is an ability that must be possessed by students to improve their English skills both oral and written. The aim of this study is to find out the implementation of tenses learning based on MATENG (Mathematic-English) formula in the English Education Study Program at Muria Kudus University. The method used is descriptive method. The results showed that: 1) the implementation of the learning model tenses using the MATENG formula (Mathematic English) includes 3 aspects; mastery of the names of 16 tenses, functions and formulas; 2) the learning process of tenses starts from appraisal, then main activity used the PPP method, and individual tasks for students; 3) the students’ response to the implementation of the learning model tenses using the MATENG formula is stated to be very good.